2016
DOI: 10.1055/s-0041-106656
|View full text |Cite
|
Sign up to set email alerts
|

HBsAg and anti-HCV screening in elderly hospitalized patients of a German tertiary referral centre

Abstract: HBsAg and anti-HCV were underdiagnosed in a senescent population, however, only few cases presented with advanced liver disease. Referrals from nursing homes were at increased risk for HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The anti-HCV prevalence in the GP ranged from 0.2 to 1.9%, and was 1.5% among baby boomers (proxy population) ( 42 ). Two studies reported an HCV RNA prevalence of 0.2% ( 5 ) and 0.4%, respectively ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-HCV prevalence in the GP ranged from 0.2 to 1.9%, and was 1.5% among baby boomers (proxy population) ( 42 ). Two studies reported an HCV RNA prevalence of 0.2% ( 5 ) and 0.4%, respectively ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…A higher prevalence is often found among males and with increasing age (5,61,62), and using baby boomers as proxy population for the GP in Germany should be carefully considered. The study which compared baby boomers and GP in this study found similar prevalence of HBsAg prevalence in the two groups, but higher anti-HCV prevalence among the German baby boomer population (42). Data from first time blood donors were included as this group is more likely to resemble the GP compared to multiple blood donors.…”
Section: Prevalence In General Populationmentioning
confidence: 90%
“…
Hepatitis B surface Antigen (HBsAg) and hepatitis C antibody (anti-HCV) assays have been performed in most laboratories using a variety of analytical methods with different reagents for Hepatitis B virus (HBV) and Hepatitis C virus (HCV) screening [1][2] . The purpose of this study was to develop an EQA program for dual HBsAg and anti-HCV serological testing to ensure the accuracy and reliability of serological assays.
…”
mentioning
confidence: 99%
“…However, older patients are candidates for elevated risk for advanced liver disease. (12).…”
mentioning
confidence: 99%